EFEKTIVITAS KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI DENGAN MOTIVASI KERJA GURU SMK SWASTA DI KOMISARIAT CIBADAK KABUPATEN SUKABUMI - Isman Kadar (Universitas Pakuan, 2014)
The research can be classified into a correlational research consist of two independent variables, namely principals transformational leadership and organizational culture, and a dependent variable, namely teachers work motivation. The research was conducted in the private vocational school at Cibadak Commissariat, Sukabumi District, West Java Province in 2014 with amount of sample 126 taken by proportional random sampling.The research used survey method and data analysis technique used single and multiple linear correlation and regression. Hypothesis testing conducted at the 0.05 significance level. The research has three conclusions namely (1) there is positive and highly significant correlation between principals transformational leadership with teachers work motivation, with correlation coefficient, ryl = 0.744 and regression equation ? = 44.505 + 0.697X1. (2) There is positive and highly significant correlation between organizational culture with teachers work motivation, with correlation coefficient, ry2 = 0.843 and regression equation ? = 25.164 + 0.885X2. (3) There is positive and highly significant correlation between principals transformational leadership and organizational culture simultaneously with teachers work motivation, with correlation coefficient, ry12 = 0.873 and regression equation ? = 15.774 + 0.290X1 + 0.661X2. Based on the conclusions, they have some implications that teachers work motivation can be increased through principals transformational leadership and organizational culture.Keywords : Transformasional Leadership, Organizasional Culture, Work Motivation